Enhanced adhesion of epoxy on a stainless steel surface treated with O2/Ar microwave plasma - Ting, Julie Anne S. (Quezon City College of Science, University of the Philippines, 2011)
The study aims to investigate the enhancement of the adhesion between a two-part steel-filled epoxy adhesive and a stainless steel surface treated with low pressure microwave plasma. Contact angle measurements show that maximum wettability of the surface was obtained at 1000 W plasma with 20 minutes of treatment time, -50 V sample bias, and 1.67% O2/Ar gas flowrate ratio, based on the lowest measured contact angle of 19.87ᵒ ad highest work of adhesion of 141.27 mN/m. Enhancement of the wettability of the steel surface is attributed to increased surface roughness and deposition of oxides on the surface. Surface roughness increased to 76.74 nm for the O2/Ar plasma treated steel surface, from 64.38 nm of the untreated steel surface as observed using atomic force microscopy. Optical emission spectroscopy shows the presence of Ar I, Ar II, O I, and O2 I species in the plasma. Oxides are also deposited on the steel surface as confirmed by energy dispersive x-ray spectroscopy. At optimum plasma conditions, tensile test results show that the adhesion strength of epoxy bonded O2/Ar plasma treated surfaces is increased to 3816.0 N, which is significantly higher compared to 3030.3 N for the epoxy-bonded untreated surfaces. Furthermore, surface energy calculations suggests that dispersive forces such as electron donor-electron acceptor interactions contribute to the formation of strong bonds at the interface between the stainless steel and the epoxy.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Adhesion; Adhesives